Comparison of BBO, WIPSO & PSO Techniques for the Optimal Placement of FACTS Devices to Enhance System Security. (2016) - Kavitha, K.; Neela, R.
Abstract: Nowadays power systems are heavily loaded and are being operated in ways not originally envisioned. Flexible AC Transmission System (FACTS) devices play a vital role in improving the static as well as dynamic performance of the power systems. FACTS devices are based on solid-state control and so the control actions at far higher speed is possible. However the location and rating of the FACTS devices play a major role in deciding the extent to which the objective of improving the system performance is achieved in a cost effective manner. In this work an objective function comprising of cost, line loadings and load voltage deviations is proposed to tap maximum benefits out of their installation and the weights assigned to them decide their relative importance. FACTS devices such as Thyristor Controlled Series Compensator (TCSC) and Static VAR Compensator (SVC) are considered. The optimization is carried out considering four parameters namely the number of FACTS device, location, type and rating of the device. In this work three cases (only TCSC, only SVC, TCSC & SVC) are considered forthe optimal placement of the devices, using PSO, WIPSO and BBO techniques.